Gastrointestinal digestion of food-use silver nanoparticles in the dynamic SIMulator of the GastroIntestinal tract (simgi®). Impact on human gut microbiota. (October 2019) - Cueva, Carolina; Gil-Sánchez, Irene; Tamargo, Alba; Miralles, Beatriz; Crespo, Julian; Bartolomé, Begoña; Moreno-Arribas, M. Victoria
Abstract: The increasing use of silver nanoparticles (AgNPs) in consumer products has led to concern about their impact on human health. This paper aims to provide new scientific evidence about the modifications and potential effects of AgNPs with food applications during their passage through the digestive tract. For that, two types of AgNPs [solid polyethylene glycol-stabilised silver nanoparticles (PEG-AgNPs 20) and liquid glutathione-stabilised silver nanoparticles (GSH-AgNPs)] were initially subjected to gut-microbial digestion simulation in an in vitro static model. Based on these experiments, digestion of GSH-AgNPs was carried out in a dynamic model (simgi ® ) that simulated the different regions of the digestive tract (stomach, small intestine and the ascending, transverse and descending colon) in physiological conditions. Dynamic transport of GSH-AgNPs in the simgi ® was similar to that observed for the inert compound Cr-EDTA, which discarded any alterations in the intestinal fluid delivery due to the AgNPs. Also, feeding the simgi ® with GSH-AgNPs seemed not to induce significant changes in the composition and metabolic activity (i.e., proteolytic activity) of the gut microbiota. Concerning monitoring of AgNps, it was observed that the GSH-AgNPs underwent several transformations in the gastrointestinal fluids and appeared to expose the intestine in ways that were structurally different from the original forms. In compliance with European guidelines, the simgi ® model can be considered a useful in vitro tool to evaluate the effects of nanoparticles at the digestive level, prior to human studies, and, therefore, minimising animal testing. Highlights: Validation of fluid dynamic transport of simgi ® using an inert compound. Usefulness of simgi ® model in the application of food-use silver nanoparticles. The AgNPs underwent several transformations during gastrointestinal digestion. The GSH-AgNPs seemed not to modify the composition and metabolic activity of human gut microbiota.